Research progress and perspectives of non-coding RNAs in primary biliary cholangitis: from mechanisms to therapeutics - Wangqi Chen; Wangqi Chen; Qinghua Li; Qinghua Li; Yuxia Xie; Yuxia Xie; Hong Zhu; Hong Zhu (Frontiers in Medicine)
Primary biliary cholangitis (PBC), an autoimmune-mediated cholestatic liver disease with a female predominance, remains enigmatic in its pathogenesis despite advances in understanding immune dysregulation, bile acid dyshomeostasis, inflammatory cascades, gut-liver axis crosstalk, and sex-biased mechanisms. Although ursodeoxycholic acid is widely recognized as the first-line therapy, its variable efficacy underscores the need for novel biomarkers and targeted therapies. Non-coding RNAs (ncRNAs), though not encoding proteins, have emerged as promising candidates due to their pivotal regulatory roles in autoimmune processes. This review systematically delineates the interplay between ncRNAs (miRNAs, lncRNAs, circRNAs) and key PBC mechanisms, evaluates their diagnostic and therapeutic potential, and proposes future research frameworks to bridge molecular insights with clinical translation.